70-year-old female presenting with rectosigmoid (colonic) xanthoma and multiple benign polyps – case report - Moran, Anna M.; Fogt, Franz (Polish Journal of Pathology, 2010)
Xanthomas are benign lesions frequently described in the upper gastrointestinal tract, most commonly in the stomach. In the stomach, these lesions are usually associated with chronic gastritis, intestinal metaplasia, H. pylori infection and duodenogastric reflux following gastric surgery, but are otherwise indolent. Xanthomas in the upper gastrointestinal tract occur in a broad age range, 45-82 years (mean: 65 years). Rare cases have also been described in the esophagus, duodenum, small intestine, colon and rectum. Rectosigmoid location of xanthomas have been described in rare cases. We present a case of polypoid xanthoma in the rectosigmoid colon occurring in a 70-year-old female with a history of hyperplastic polyps.